Diploma No Problem : Can Private Schools Be of Lower Quality than Public Schools? - Giorgio Brunello; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2004)
Motivated by anecdotal as well as econometric evidence from Italy, we ask whether private schools can provide lower quality than public schools. Using a stylized model of the education market with sequential entry of a public and a private school, we show that, depending on the underlying parameters of the model, a market structure with the private school offering at a positive price lower quality than the public school can be an equilibrium. The calibrated parameters for Italy suggest the existence of such an equilibrium in the Italian market for education.
Keywords: H73; H52; 330; education; private schools; Italy; Privatschule; Allgemeinbildende Schule; Dienstleistungsqualität; Bildungsniveau; Schätzung; Italien